(3OjhGf MGRe GdbQWGLfj Ch GdbUjOI GdCdajIs - (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdMeO ddg GdPj CfWbfG HCaUM GdCdSf CeG HYO(B: (3aEfj CQjO Cf CfU aj gPG GdeLehY, hCNdb aj gPG GdehVhY agj ef JfGSH CdaGXgG hJfGSb CZQGVgG s
(3BNQgG (B:s
(3hGaJM dfG HGH QMeGc GdJj hSYJ Cgd GdNWGjG hHGdMSfi dfG CNJJe s
(3HgG HYV GdVHWs
(3hGdebUhQI aj eOM GdeSJfUQ eMeO Hf jMji GdQVj GdMaUj edc JhfSs
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B159s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B76 s
Keywords: (3GdCOHs